Gold-Sensitized Silicon/ZnO Core/Shell Nanowire Array for Solar Water Splitting - Zhang, Fu-Qiang; Hu, Ya; Sun, Rui-Nan; Fu, Haoxin; Peng, Kui-Qing (Frontiers in Chemistry, 2019)
Solar water splitting represents one of the most promising strategies in the quest for clean and renewable energy. However, low conversion efficiency, use of sacrificial agents and external bias for current water splitting system limit its practical application. Here, a gold-sensitized Si/ZnO core/shell nanowire photoelectrochemical (PEC) cell is reported for efficient autonomous solar water oxidation. We demonstrated gold-sensitized n-Si/n-ZnO nanowire arrays exhibited higher energy conversion efficiency than gold-sensitized p-Si/n-ZnO nanowire arrays due to the favorable energy-band alignment characteristics. Without any assistance from an external electrical source and sacrificial reagents, gold-sensitized n-Si/n-ZnO core/shell nanowire array photoanode achieved unbiased water splitting under simulated solar light illumination. This method opens a promising venue to cost-efficient production of solar fuels.